Multifunctional, JNK-inhibiting nanotherapeutics for augmented elastic matrix regenerative repair in aortic aneurysms - Camardo, Andrew (Drug Deliv Transl Res, 2018)
Growth of abdominal aortic aneurysms (AAA), localized aortal wall expansions, is driven by the disruption and subsequent loss of aortal wall elastic fibers by matrix metalloproteases (MMPs). Since elastic fibers do not naturally regenerate or repair, arresting/reversing AAA growth has not been possible. Previously, we showed utility of doxycycline (DOX), an MMP inhibitor drug, to stimulate elastic matrix neoassembly and crosslinking at low μg/ml doses in addition to inhibiting MMPs. We currently show in aneurysmal smooth muscle cell (SMC) cultures, that effects of exogenous DOX in this dose range are linked to its upregulation of transforming growth factor beta (TGF-β1) via its inhibition of the regulatory protein c-Jun-N-terminal kinase 2 (JNK 2). We have identified a DOX dose range that stimulates elastogenesis and crosslinking without adversely impacting cell viability. Using JNK 2 inhibition as a metric for pro-regenerative matrix effects of DOX, we further demonstrate that sustained, steady state release of DOX at the useful dose, from poly(ethylene glycol)-poly(lactic glycolic acid) nanoparticles (NPs) provides pro-elastogenic and anti-proteolytic effects that could potentially be more pronounced than that of exogenous DOX. We attribute these outcomes to previously determined synergistic effects provided by cationic amphiphile groups functionalizing the polymer NP surface. Released DOX inhibited expression and phosphorylation of JNK to likely increase expression of TGF-β1, which is known to increase elastogenesis and lysyl oxidase-mediated crosslinking of elastic matrix. Our results suggest that JNK inhibition is a useful metric to assess pro-elastic matrix regenerative effects and point to the combinatorial regenerative benefits provided by DOX and cationic-functionalized NPs.